2010
DOI: 10.1007/s00221-010-2263-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related kinematic changes in late visual-cueing during obstacle circumvention

Abstract: On a daily basis, we are challenged by common environmental obstacles (e.g. street posts) that require simple and often rapid modifications to our gait patterns to avoid collisions. Poor vision appears to be responsible for important reductions in postural stability during gait; and therefore, individuals with impaired vision, such as the elderly, may be at a greater risk of falling, especially under conditions where stepping avoidance strategies may be constrained by the environment. The purpose of the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Findings from the reviewed studies (Paquette and Vallis, 2010;Petrofsky et al, 2004) confirm locomotion biomechanics to change with age (Bosse et al, 2012;Elble et al, 1991;Judge et al, 1996). Additionally, such changes appear to occur with concurrent adjustments in eye movements and visual focus.…”
Section: Duration Of Fixations Saccadic Latencysupporting
confidence: 58%
See 3 more Smart Citations
“…Findings from the reviewed studies (Paquette and Vallis, 2010;Petrofsky et al, 2004) confirm locomotion biomechanics to change with age (Bosse et al, 2012;Elble et al, 1991;Judge et al, 1996). Additionally, such changes appear to occur with concurrent adjustments in eye movements and visual focus.…”
Section: Duration Of Fixations Saccadic Latencysupporting
confidence: 58%
“…Kinematic data reported in the reviewed studies suggest that older adults tend to be more cautious during locomotion, as demonstrated by reduced step length and walking speed, presumably to increase gait stability when preparing to avoid an obstacle (Paquette and Vallis, 2010). Walking speed is likely reduced in older adults because of associated prolonged stance time and greater number of steps for a given distance (Petrofsky et al, 2004).…”
Section: Duration Of Fixations Saccadic Latencymentioning
confidence: 95%
See 2 more Smart Citations
“…In the presence of uneven surfaces, for example, they have been shown to decrease their walking speed and their step length more than younger adults do (Marigold and Patla, 2008). Moreover, older adults have been found to spend more time looking at the ground during obstacle avoidance, whereas younger adults spend more time gazing straight ahead (Paquette and Vallis, 2010). Finally, the maintenance of a large personal space between themselves and other pedestrians is another strategy used by older adults to reduce the risk of bumping into someone and falling (Gérin-Lajoie et al, 2006).…”
Section: Obstacle Negotiationmentioning
confidence: 99%